Optimization of a drug transporter probe cocktail: potential screening tool for transporter‐mediated drug–drug interactions. (21st June 2018) - Stopfer, Peter; Giessmann, Thomas; Hohl, Kathrin; Hutzel, Sabine; Schmidt, Sven; Gansser, Dietmar; Ishiguro, Naoki; Taub, Mitchell E.; Sharma, Ashish; Ebner, Thomas; Müller, Fabian
Abstract : Aims: Previous pharmacokinetic characterization of a transporter probe cocktail containing digoxin (P‐gp), furosemide (OAT1, OAT3), metformin (OCT2, MATE1, MATE2‐K) and rosuvastatin (OATP1B1, OATP1B3, BCRP) in healthy subjects showed increases in rosuvastatin systemic exposure compared to rosuvastatin alone. In this trial, the doses of metformin and furosemide as putative perpetrators were reduced to eliminate their drug–drug interaction (DDI) with rosuvastatin. Methods: In a randomized, open‐label, single‐centre, five‐treatment, five‐period crossover trial, 30 healthy male subjects received as reference treatments separately 0.25 mg digoxin, 1 mg furosemide, 10 mg metformin and 10 mg rosuvastatin, and as test treatment all four drugs administered together as a cocktail. Primary pharmacokinetic endpoints were AUC0‐tz (area under the plasma concentration–time curve from time zero to the last quantifiable concentration) and C max (maximum plasma concentration) of each probe drug. Results: Geometric mean ratios and 90% confidence intervals of test (cocktail) to reference (single drug) for AUC0‐tz were 96.4% (88.2–105.3%) for digoxin, 102.6% (93.8–112.3%) for furosemide, 97.5% (93.5–101.6%) for metformin and 105.0% (96.4–114.4%) for rosuvastatin, indicating lack of interaction. The same analysis for C max and for pharmacokinetic parameters of urinary excretion of all cocktail components also indicated no DDI. Conclusions: Digoxin (0.25 mg), furosemide (1 mg), metformin (10 mg) and rosuvastatin (10 mg) exhibit no mutual pharmacokinetic interactions and are well tolerated administered as a cocktail. The cocktail is thus optimized and has the potential to be used as a screening tool for clinical investigation of transporter‐mediated DDI.